Potential Identification Of Coardd Land As A Basis For Increasing Food Production And Family Income In Tebing Tinggi Okura Ward, Pekanbaru City During The Covid-19 Pandemic - Mufti Mufti; Niken Nurwati (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Yard land is land that is around the household, usually has an ownership relationship with the owner of the house. In Tebing Tinggi Okura Ward, Rumbai Pesisir District, there are 6 hamlets (RW) located in 19 Neighborhood Units (RT), 655 Family Heads (KK). The aims of this research are to: 1). Identifying the Potential of the Yard in Tebing Tinggi Okura Village, Pekanbaru City. 2). Analyzing the availability of family labor in yard empowerment in Tebing Tinggi Okura Village, Pekanbaru City. 3). Knowing the obstacles in empowering the yard in the Tebing Tinggi Okura Village, Pekanbaru City. The research was carried out using a survey method. The unit of analysis in this study is the household. Sampling by purposive sampling is based on the area of ​​the yard in the selected hamlets. The data collected in this study include primary data and secondary data. The data obtained in this study were processed descriptively and quantitatively. The results of the research and data analysis can be concluded as follows: The interest of the sample of households towards the empowerment of their yard to increase food production and family income in Tebing Tinggi Okura Ward, Pekanbaru City increased compared to the percentage of sample households that had empowered their yard at the time of the study. The average potential for family labor in yard empowerment in Tebing Tinggi Okura Village, Rumbai Timur District, Pekanbaru City is 73.27 HKP/year. This potential can be used to realize interest in empowering the yard by developing the cultivation of vegetable and secondary crops to increase household food production and increase family income. Pekanbaru City includes land that is less fertile, lacks capital. It is recommended to improve education, assistance and assistance to households in Tebing Tinggi Okura Village, Rumbai Timur District in yard empowerment activities to increase household food production and increase family income.